Rediscovery of Pogostemon nilagiricus (Lamiaceae), a steno-endemic and critically endangered aromatic species - Murugan, R.; Ravikumar, K.; Livingstone, C. (Rheedea, 2010)
Pogostemon nilagiricus Gamble (Lamiaceae) is rediscovered from Nilgiri hills, the type locality, after a gap of 97 years. A detailed description, photograph and note on its taxonomy are provided. Current threat status has also been assessed based on the recent botanical explorations.